PENGARUH LAYANAN INFORMASI TENTANG TUGAS PERKEMBANGAN REMAJA TERHADAP PEMAHAMAN TUGAS-TUGAS PERKEMBANGAN DI SMA - Maulida, Nur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to determine the influence of information Service About Tasks of Youth Development toward the understanding of students development tasks in class X of SMA Negeri 1 Sungai Raya. The method used was descriptive method in the form of survey research. The population in this study was 297 and the sample was 55 students from SMA Negeri 1 Sungai Raya. This research used quantitative approach. Data collection technique in the form of questionnaire. While the technique of data analysis used was percentage formula. Based on the results of this study, the influence of information service about task of youth development towards the understanding of students development tasks reached 52% . This showed that the influence of information services on the task of youth development toward the understanding of tasks development was and the service activities have been implemented well too. Keywords: Information Service, Task of Youth Development.